A implementa????o do ensino fundamental de nove anos na rede municipal de ensino de S??o Paulo - Machado, Rosangela Aparecida dos Reis (2016)
The present work aims at understanding the processes behind the adoption of the nine-year cycle for the Fundamental Education in the City of Sao Paulo. It takes into consideration the several possible mediations between an affirmative kind of politics (such as those proposed by international organisms), the creation of national politics on longer periods of mandatory Fundamental Education and the effectiveness of such politics on a micro level. In order to do so the theoretical basis to which we refer to is that on the cycle of politics as posed by Stephen Ball. Our object is Sao Paulo???s Public Education System, the role model for other Schools throughout the State of Sao Paulo due to the large area it serves. Documental and bibliographical analysis, as well as semi structured interviews and focal groups studies were selected as methodological procedures. Focal groups were made up by First and Second Grade teachers as well as School managers. The results were presented in four different chapters. The first chapter contemplates the context and the international documents that theoretically justify the need to extend mandatory education from eight to nine years. It also deals with the main actions taken by the Brazilian government as established by different accords signed by our country. The second chapter evolves around official Brazilian documents produced in order to legalize the nine-year fundamental education system. The third chapter briefly describes the History of the Secretary of Education of Sao Paulo. It also presents the legislation and other documents produced by the City about the nine-year cycle. The fourth chapter analyses the path towards the nine-year cycle in the City of Sao Paulo, taking into consideration the cycle of politics. The data collected during the research support Ball???s theory that the process of translating practices from politics is extremely complex as it involves interpreting several different subjects. Thus, the completion of the nine-year cycle in the Fundamental Educational level in the City of Sao Paulo still presents several challenges, such as consolidating a model for infancy pedagogy, building a new curriculum, solidifying its program in the educational unities that deal with the formation of teachers as well as the adequacy of spaces and time slots.